EVALUASI PENGELOLAAN SEDIAAN FARMASI DI GUDANG INSTALASI FARMASI RSUD DR. DRAJAT PRAWIRANEGARA SERANG-BANTEN TAHUN 2022 - Yusransyah, Yusransyah; Herawati, Fera; Noviyanto, Fajrin; Udin, Baha; Stiani, Sofi Nurmay (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Pharmaceutical supply management is a series of sequential actions that begin with the procurement of drugs, the act of receiving drugs, and the process of storing drugs. This study aims to evaluate the suitability of pharmaceutical preparation management process at the Pharmacy Installation, Regional General Hospital dr. Drajat Prawiranegara in 2022 according to the provisions of the Regulation of the Minister of Health of the Republic of Indonesia Number 72 of 2016. The research method is explained quantitatively through selecting information, carried out in observation as an assessment and analysis of suitability. After the evaluation, aspects of the procurement process were identified that met the standards, including the high frequency of procurement per drug item (48 times per year), complete orders or invoices, and no late payments from the hospital. The aspect of the receiving process has also met the standards. That is, all drug orders are by the goods received. The storage process has met the standards, namely all goods according to the stock card, while the Turn Over Ratio (TOR) aspect has not met the standards with a value of 3.91 times. The warehouse management system uses First In First Out (FIFO) and First Expired First Out (FEFO). The percentage of damaged or expired drugs and the percentage of non-spinning stock is 0%. The conclusion of this research is the process of procuring and receiving drugs at IFRS dr. Dradjat Prawiranegara Serang has followed the guidelines, but in the TOR aspect it has not met the standards.